Philanthropy in the Millennial Age: Trends toward Polycentric Personalized Philanthropy. - CRAWFORD, ELIZABETH CRISP; JACKSON, JEREMY (Independent Review)
The article discusses how social media have emerged as a new public square within which polycentric organization is a natural feature. It notes that the organizations that will effectively reach the millennial market are those that adopt more polycentric and personalized approaches to their IMC efforts. It adds that the facilities of social media promotion are the Internet and the software, programs, and applications that join users together.